PENGARUH DOSIS DAN SAAT PEMBERIAN PUPUK ORGANIK PADAT TERHADAP PERTUMBUHAN DAN HASIL TANAMAN BAWANG MERAH ( Allium Ascalonicum L.) - Samuel Randamuluk; AF Aziez AF Aziez; SUSWADI SUSWADI (JURNAL ILMIAH AGRINECA, 2012)
The aims for knowing the influence of dosage and moment giving solid organic vertilizer towards the growth and the result of onion plant ( allium ascalonicum.l. ) this research has been conducted in klodran village , colomadu subdistrict, karanganyar regency on the height of 120 meters above surface of the sea, on regosol land from agustus st until October 1 st,2009 This research uses factorial method with basic pattern random basic planning complete group, consists of 2 treatment factors and 3 times of repetition. The firt factor of dosage of solid organic fertilizerÂ  ( D ) consists of four levels ( D1 ) = 10 ton / hectare ,D2 = 20 ton hectare, D3 = 30 ton / hectare ; D4 = 40 ton / hectare , the second factor, moment giving solid organic fertilizer consists of 3 levels ; S1 = 2 weeks before planting , S2 = 1 vweek before planting, S3 = together with planting. The dosage treatment of solid organic fertilizer influences unreal towards the height of plant, the weight of fresh brancast , yhe weight of dry brancast, the amount of tuber per clumb, the amount of tuber pe land , the weight of fresh tuber per clumb, the weight of dry tuber per clumb, the weight of fresh tuber per land, the wight of dry tuber per land. The treatment on the moment giving solid organic fertilizer influences unreal towards the height of pland, the weight of fresh brancast, the weight of dry brancast, the amount of tuber per clumb, the amount of tuber per land, the weight of fresh tuber per clumb, the weight of dry tuber per clumb, the weight of fresh tuber per land, the weight of dry tuber per land. The interaction between dosage and moment giving solid organic fertilizer influences unreal towards the heigh of pland , the amount of tuber per clumb, the amonnt of tuber per land , the weight of fresh tuber per clumb, the weight of dry tuber per clumb, the weigh of fresh tuber per clumb, and influences real towards the weight of fresh brancast, the weight of dry brancast, the weight of dry tuber per land. The highest weight of dry tuber is 1,46 kgs / land ( 10,96 ton / hectare), got on the combined treatment D3S2 ( the dosage of 30 ton / hectare and 1 week before planting ) while, the lowest weight of dry tuber is 1,13 kgs / land ( 8,47 ton / hectare ) got on the combined treatment D1S2 ( the dosage of 10 ton / hectare andÂ  week before planting ).